Pengaruh Pergantian Manajemen, Kepemilikan Publik dan Financial Distress terhadap Auditor Switching - Rosella Aprilia; Bahtiar Effendi (Universitas Matana, 2019)
Auditor switching is the change of auditor or Public Accountant Firm which conducted by company. The purpose of this research is to get the empirical evidence about : (1) The influence of The Change of Management to Auditor Switching, (2) The influence of Public Ownership to Auditor Switching, (3) The influence of Financial Distress to Auditor Switching, The influence of The Change of Management, Public Ownership, and Financial Distress simultaneously to Auditor Switching, in Manufacture Companies which listed in Indonesia Stock Exchange (IDX) periode 2013 – 2017. The population in this research are The Manufacture Companies which listed on the Indonesia Stock Exchange in 2012-2016. Sampling technique that used in this study was purposive sampling technique, where as 32 manufacture companies are the sample in this research, with the total observation are 155 observations. Data analysis techniques are logistic regression analysis. The result of this research shows that : (1) The Changes of Management doesn’t influence to Auditor Switching, (2) Public Ownership doesn’t influence to Auditor Switching, (3) Financial Distress doesn’t influence to Auditor Switching, (4) The Change of Management, Public Ownership and Financial Distress don’t influence simultaneously to Auditor Switching.